In vitro assessment of antioxidant and photoprotective activities of torch ginger leaf extract (Etlingera elatior (Jack.) R.M.Sm.) - Taurhesia, Shelly; Kristanty, Yosepha; Winsari, Crisya (Universitas Ahmad Dahlan, 2025)
The torch ginger plant (Etlingera elatior (Jack) R.M.Sm.) is a member of the Zingiberaceae family and is frequently called kecombrang in Java. This plant has been used as a traditional medicine and food flavor enhancer but is limited as a cosmetic ingredient. Flavonoids and phenolic compounds are examples of secondary metabolites found in this plant. Most flavonoid compounds show sunscreen activity due to the chromophore groups (conjugated single double bonds) capable of absorbing UV A and UV B radiation. According to BPOM Decree No. 17/2022, only listed ingredients in Annex 4 are considered as UV filters but natural herbal compounds with antioxidant properties are applied as sunscreens. This study focused on the in vitro assessment of antioxidant and photoprotective activity from E. elatior leaf extract. First, extracting a 70% ethanol extraction of torch ginger leaves, then evaluated the extract’s quality, its antioxidant activity via the DPPH assay, and its in-vitro photoprotective activity using a UV spectrophotometer. The results showed that the extract from E. elatior leaves possesses remarkably strong antioxidant properties, as shown by its IC50 value of 47.46 μg/mL, and the extract at concentration of 1000 μg/mL provided photoprotection activity calculated as an SPF of 24.05 (ultra protection), erythema transmission value of 1.18% (extra protection) and pigmentation transmission value of 3.49% (total block). It can be concluded that torch ginger leaf extract has high potential as a cosmetic natural ingredient because of very strong antioxidant activity and photoprotective ultra protection.